Research on the method of quantitative evaluating material hardness and tensile strength by critically refracted longitudinal wave. (February 2020) - Men, Ping; Dong, Shiyun; Kang, Xueliang; Yan, Shixing; Cheng, Zhiyuan; Lv, Ruiyang
Abstract: Hardness and tensile strength are the important parameters to assess the performance mechanical materials, there are many challenges to evaluate mechanical properties of materials by ultrasonic testing method. In this paper, high-precision critically refracted longitudinal wave measurement system was set up, ultrasonic wave propagation time of different heat treated 45 steel calibration specimens were measured by double probes method, and ultrasonic velocity was calculated. The distance between transmitting probe and receiving probe was changed to look for optimum distance for measuring critically refracted longitudinal wave velocity, on the above basis, the effects of different microstructure for velocity were studied. The mapping relationship among material hardness, tensile strength, microstructure and critically refracted longitudinal wave velocity were obtained, and calibration models for evaluating the hardness and tensile strength were established and verified. To further reduce the tensile strength prediction error, the hardness and tensile strength of 45 steel calibration specimens was built up, combined hardness calibration model, improved tensile strength calibration model was obtained. The hardness and tensile strength prediction error by the calibration model basically meets the error requirement of 10% for engineering application.